O USO DO ULTRASSOM NO PÓS-OPERATÓRIO DE LIPOASPIRAÇÃO: REVISÃO DE LITERATURA - Mocelin, Kênia D.; Korte, Fernanda d. L.; Schmitt, Josieli S.; Oliveira, Vanessa C.; Eickhoff, Heloísa M. (Salão do Conhecimento, 2013)
Resumo